The discomfort with representative democracy. Trust in democracy and desired reforms in Austria - Grössenberger, Ines; Pausch, Markus (Momentum Quarterly, 2018)
According to all relevant democratic measurements, Austrian democracy is one of the best in the world. It has also improved significantly over time according to objective criteria. Nevertheless, it has become apparent in recent years that the population is less and less satisfied with the functioning of representative democracy in Austria (as in other European countries) and has less confidence in democracy as a whole. This article analyses some of the common explanations for the loss of confidence and shows the reform wishes of the population along various sociodemographic characteristics. Data from representative surveys conducted in 2008 and 2016 on behalf of the Centre for Future Studies at Salzburg University of Applied Sciences will be used for this purpose. These data are compared with each other and with other data from EU-SILC, the Eurobarometer and instruments on democracy quality such as the Freedom House Index or the Democracy Barometer.